Developing a culturally tailored short message service (SMS) intervention for improving the uptake of cervical cancer screening among Ghanaian women in urban communities - Harriet Affran Bonful; Adolphina Addoley Addo-Lartey; Ransford Selasi Sefenu; Adanna Nwameme; Timothy Agandah Abagre; Adolf Kofi Awua; Nii Armah Adu-Aryee; Florence Dedey; Richard Mawuena Kofi Adanu; Kolawole Stephen Okuyemi (BMC, 2022)
Abstract Background There has been extensive research across the globe to understand the barriers and facilitators of cervical cancer (CC) screening. However, few studies have focused on how such information has been used to develop text messages for mHealth screening programs, especially in resource-poor countries. This study elicited information on barriers and facilitators, the preferences of women regarding the modalities for delivery of health SMS messages on screening for cervical cancer, and demonstrates how this information was used to create a health screening program among women in the Greater Accra Region of Ghana. Methods Four main activities were carried out, including (1) a total of five focus group discussions, (2) a baseline survey involving 62 female bankers and 68 women from the communities, (3) a stakeholder meeting involving experts in cervical cancer research and clinical care, and (4) pilot testing of the text messages. Focus group discussions and the baseline survey data were collected concurrently between February and May 2017 and the results were used to develop 5 specific communication objectives during the stakeholder engagements held in June 2017. Results In all, 32 text messages were developed and pretested in July 2017(13 addressed knowledge on CC; 6 highlighted the importance of early detection; 5 allayed fear as a barrier to CC screening; 5 encouraged women to have time for their health, and 3 messages contained information on where to go for screening and the cost involved). Although awareness about the disease was high, knowledge of CC screening was low. For two-thirds of respondents (22/33), perceived lack of time, high cost, and fear (of cc, screening procedure, and potential for negative outcome) accounted for the reasons why respondents will not go for screening, while education on CC, especially from health workers and the mass media enabled uptake of CC screening. Conclusion Several factors prevent women from accessing screening services for CC, however, barriers such as low levels of education on CC, lack of time, and fear can be targeted in SMS messaging programs.